2011
DOI: 10.1016/j.yjmcc.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging of cardiac hypoxia: Opportunities and challenges

Abstract: Myocardial hypoxia is a major factor in the pathology of cardiac ischemia and myocardial infarction. Hypoxia also occurs in microvascular disease and cardiac hypertrophy, and is thought to be a prime determinant of the progression to heart failure, as well as the driving force for compensatory angiogenesis. The non-invasive delineation and quantification of hypoxia in cardiac tissue therefore has the potential to be an invaluable experimental, diagnostic and prognostic biomarker for applications in cardiology.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 105 publications
1
60
1
Order By: Relevance
“…In this study, we identified a key hypoxic threshold that induces the major hallmarks of compromised but salvageable myocardium: depressed contractile function, compromised phosphocreatine levels (but stable ATP levels), elevated HIF-1a expression, and increased but not maximal lactate washout (indicating residual oxidative reserve). At this threshold, achieved by perfusion with KHB saturated with 30% O 2 , we demonstrated that 64 Cu-CTS is the only complex among the 4 evaluated that provides a hypoxic-to-normoxic tissue contrast that would be exploitable for PET imaging (9).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In this study, we identified a key hypoxic threshold that induces the major hallmarks of compromised but salvageable myocardium: depressed contractile function, compromised phosphocreatine levels (but stable ATP levels), elevated HIF-1a expression, and increased but not maximal lactate washout (indicating residual oxidative reserve). At this threshold, achieved by perfusion with KHB saturated with 30% O 2 , we demonstrated that 64 Cu-CTS is the only complex among the 4 evaluated that provides a hypoxic-to-normoxic tissue contrast that would be exploitable for PET imaging (9).…”
Section: Discussionmentioning
confidence: 91%
“…In the one very small (7-patient) cardiac clinical trial that has been performed to date using 62 Cu-ATSM, 62 Cu accumulation was visualized in the myocardium of only 1 patient with unstable angina, despite 4 of those patients exhibiting increased regional 18 F-FDG uptake (12). Thus, whereas 64 Cu-ATSM can be used to selectively identify the extreme acute hypoxia commonly induced in experimental models, it seems insufficiently sensitive to detect the subtle hypoxia characterizing the chronic cardiac ischemic syndromes that are currently difficult to identify (9).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[94] However, nitroimidazoles present a number of disadvantages for routine use, such as their low lipophilicity, slow pharmacokinetics, low tumor-to-muscle ratios, and limited clearance from normoxic tissue. [95,96] Bis(thiosemicarbazonato) complexes for the imaging of hypoxia were first employed by Fujibayashi et al in 1997 in a rat heart ischemic model.…”
Section: Imaging Of Hypoxia With Atsm Complexesmentioning
confidence: 99%